If it's not what You are looking for type in the equation solver your own equation and let us solve it.
2x+1x+6=3(x+2)
We move all terms to the left:
2x+1x+6-(3(x+2))=0
We add all the numbers together, and all the variables
3x-(3(x+2))+6=0
We calculate terms in parentheses: -(3(x+2)), so:We get rid of parentheses
3(x+2)
We multiply parentheses
3x+6
Back to the equation:
-(3x+6)
3x-3x-6+6=0
We add all the numbers together, and all the variables
=0
x=0/1
x=0
| (2x+12)(5x−9)=180 | | 2r−2=2r= | | 3.5+7(0.25x)=2.5x | | 16+s/2=17 | | a) 3X-1=2X+2 | | 1-9b=-10b-7 | | 50+15+0.25x=40+0.35 | | 3x+6=2x+10+x-4 | | a) 3X-1= 2X + 2 | | (2x-16)=(5x-17) | | (8x-21)+(23x-16)=180 | | M=412m-4 | | 2x+3-6x=x-5x+3 | | 4(4n-8)=-16+8n | | 1/2x+1/30x+1/3x=31 | | -4(3+8m)=180 | | 5z+8+6z=52 | | -2(-2x-3)=-2x+6 | | X(5x+10)=10x+405 | | 2w+4=10w= | | -6x-21=51=3x | | 3x-2(x+6.5)=25.5 | | 2x-9/9=15/5 | | 13x+62=18x+32 | | -4=7m-18 | | 2n-1+7=2n+6 | | a) 3X - 1 = 2X + 2 | | 4c=11 | | 14-9r=r-7-9 | | x-8/12=3 | | -37-5x=3(8x-6) | | -5a+7=4a+88 |